Constitutionalization of National Minority Rights in BRICS Countries (Brazil, India and Russia) - A. Kumar; V. Rudenko; N. Filippova (BRICS Law Journal, 2021)
On the basis of comparative law, this paper analyzes the issues of national minorities in three BRICS member-states (Brazil, India and Russia), and considers the directions and trends of the constitutionalization of national minority rights in these states. The authors argue that the coordination of the interests of industrial companies, regional communities and national minorities, alongside the establishment of common standards between BRICS are vital in order to ensure the sustainable growth of the economies of its member-states. The main comparison criteria are as follows: the understanding of the term “national minority” in diﬀerent jurisdictions; the delimitation of powers of federative and regional authorities; a list of national minority rights; and instruments of representation and legal protection of national minorities. In regards to Brazil, this article focuses on the impact of the historic concept of racial democracy on contemporary policy on the issues of national minorities. For India the focus is on case law of the Supreme Court on minority issues, and for Russia the focus is on the protection of indigenous “small-numbered” peoples. The authors conclude that the direction of the constitutionalization of national minority rights diﬀers dramatically in Brazil, India and Russia. Therefore, it is necessary to provide a common understanding of the purpose of such constitutionalization, which is namely, to preserve the identity of such minorities in the process of their gradual involvement in modern economic structures and national processes.